TiO2 Catalysed Photo-oxidation of Dimethylglyoxime - Khandelwal, R.K.; Vaidya, V.K. (Asian Journal of Chemistry, 2010)
The catalysed photo-oxidation of dimethylglyoxime in near UV-TiO2 system has been studied. The yield of photoproduct increases as the substrate concentration increases up to a certain limit, and the same observation has been observed with the photocatalyst TiO2, while photocatalyst having more band gap and solvents having high dielectric constant enhance the yield of photoproduct. A probable mechanistic path has been proposed by considering these observations.